Pengaruh Pendekatan Spiritual Muhasabah terhadap Penurunan Tingkat Kecemasan pada Penderita Gangguan Medis Usia Dewasa Madya - Melati Garnis Waninggil; Luluk Masluchah; Erma Nursanti (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to examine the effect of muhasabah therapy on reducing anxiety levels among middle-aged adults with medical disorders. The proposed hypothesis states that muhasabah therapy has a significant effect on lowering anxiety levels in this group. The research subjects consisted of middle-aged adult respondents with medical conditions selected through purposive sampling. A quantitative method with a one-group pretest-posttest design was employed. The instrument used was an anxiety scale, and data were analyzed using the Paired Sample T-Test with SPSS software. The results showed a t-value of 7.617 with a significance level of p = 0.000 (p < 0.05), indicating a significant effect of muhasabah therapy on reducing anxiety levels among respondents. These findings demonstrate that muhasabah, as a spiritual approach, is effective in lowering anxiety among middle-aged adults with medical disorders, thus supporting the proposed hypothesis.